2014
DOI: 10.18034/mjmbr.v1i1.370
|View full text |Cite
|
Sign up to set email alerts
|

Core Decompression by Laser Osteoperforation: A Preliminary Report of New and Minimally Invasive Modality for the Treatment of Avascular Necrosis of the Femoral Head

Abstract: Introduction: Avascular necrosis (AVN) of the femoral head is a devastating disease that often leads to the destruction of the hip. Core decompression of femoral head is the commonest of all conservative surgical treatments where an 8-10 mm cylindrical core of bone is removed from antero-lateral segment of the femoral head. But it is employed only in early stages of the disease and its results are still of controversial efficacy and most of patients ultimately require total hip arthroplasty. Laser irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The Bangladesh Labor Code, 2006 is latest law passed by the parliament regarding labor code and henceforth it has been used as the basis for analysis and research in this thesis paper. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] We aimed our best in this research to study the health and safety hazards of garments workers predicated on the participation of workers and managers. We found that most of the factories are maintaining the standard health and safety programs in terms of the BLA, 2006, though many of the factories did not comply with all issues and guidance mentioned in the BLA, 2006.…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…The Bangladesh Labor Code, 2006 is latest law passed by the parliament regarding labor code and henceforth it has been used as the basis for analysis and research in this thesis paper. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] We aimed our best in this research to study the health and safety hazards of garments workers predicated on the participation of workers and managers. We found that most of the factories are maintaining the standard health and safety programs in terms of the BLA, 2006, though many of the factories did not comply with all issues and guidance mentioned in the BLA, 2006.…”
Section: Discussion and Recommendationmentioning
confidence: 99%